Advancement in Forensic Entomology: Techniques and Applications - Deshmukh, Gauri; Parkhe, Devyani (Microbiology and Biotechnology Research: An Overview Vol. 2, 2025)
Forensic Entomology plays a very important role in forensic science. It provides valuable inputs for crime scene investigation. This involves looking into the many pest species that are commonly related to dead bodies, as well as their life cycles and biological presence in a specific environment. One of the key concerns of forensic entomologists’ practical knowledge about the entomological evidence while collecting the insects and other biological fluids from the crime scene, their collection and preservation is a major part for entomologists. Collection of entomological evidence may be in different stages of eggs, maggots, pupae, adults and different areas of cadavers and surrounding environment. Collected samples provide critical information about injuries, time since death, and possible locations of a crime. This study covers the concepts of forensic entomology, stages of decomposition and the latest techniques used by entomologists. Additionally, the different techniques that are used to examine the entomological evidence, such as molecular analysis, enterotoxin analysis, Micro CT, cuticular hydrocarbon analysis, etc. have been discussed. Moreover, this study highlights the factors affecting PMI estimates and analyzes the uses of entomological data in PMI estimation. The main task is to determine the age of the insects. These advantages and disadvantages of age-determined methodologies are discussed in detail. The aim of this chapter is to summarize techniques that have so far been used commonly and all the latest advances made in the concerned field. All these methods have shown more reliable results, adequate accuracy and more effectiveness. As evidence contamination is a major setback in providing results, these techniques have less risk of contamination of evidence and have also proved to be less time-consuming. Through the content, readers will gain knowledge of the developments in the forensic entomology field and how they affect the preciseness and effectiveness of crime scene investigations.